1980
DOI: 10.1002/star.19800320506
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and 13C‐NMR Spectroscopy of Methylated beta‐Cyclodextrins

Abstract: The methylated analogues of P-cyclodextrin dissolve in cold water 10 -20 times better than P-cyclodextrin itself, however, quite unusually on heating they crystallize from the solution. The structure of heptakis-(2,6-di-O-methyl)and heptakis-(2,3,6-tri-O-methyl)-Pcyclodextrin was proved by gas-liquid chromatographic and 'H-NMR and ' T -N M R spectroscopic investigations. The corresponding model compounds were synthetized and, according to 13C-NMR spectroscopic investigations, a part of the so far published N M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…After drying on MgSO 4 , the chloroform layer was evaporated until dryness. The residue was washed with a mixture of diethyl ether/n-pentane (1:1); mp, 154-1607C; yield, 81% [28][29][30]. The so obtained randomly methylated CDs were fractionated by flash silica gel column (ICN, Costa Mesa, CA, USA; 0.032-0.063 mm grain size) chromatography applying a gradient of ethyl acetate and methanol 1:0-1:1.…”
Section: Synthesis Of the Randomly Methylated CDmentioning
confidence: 99%
“…After drying on MgSO 4 , the chloroform layer was evaporated until dryness. The residue was washed with a mixture of diethyl ether/n-pentane (1:1); mp, 154-1607C; yield, 81% [28][29][30]. The so obtained randomly methylated CDs were fractionated by flash silica gel column (ICN, Costa Mesa, CA, USA; 0.032-0.063 mm grain size) chromatography applying a gradient of ethyl acetate and methanol 1:0-1:1.…”
Section: Synthesis Of the Randomly Methylated CDmentioning
confidence: 99%
“…The permethylated CDs were obtained according to a procedure described in the literature. 9 The CDs were lyophilized prior to the preparation of solutions for NMR spectroscopy. Racemic and pure substrates were synthesized in our laboratory as described below.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…and the corresponding alkyl halide followed by regioselective reduction with NaBH 4 (Scheme 2) and the native CDs were permethylated with MeI. 9 All compounds were characterized by mass spectrometry (MS), 1 H and 13 C NMR spectral data and compared with data in the literature. 10 The enantiomerically pure compounds C -1 and C -3 were obtained by bioreductions of the corresponding ketones (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…We then used combined 1 H and 13 C NMR spectrometry analysis, which is a powerful technique, to furnish the number of nonequivalent protons and carbon atoms. Furthermore, the NMR analysis results give a stronger argument for the assignment of the substituted groups, and NMR has already been successfully used by Szejtli 17 and Hirayama 18 to elucidate CD derivative structures. DS by NMRsThe NMR spectra of Et--CD in CDCl 3 are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 96%
“…17 Indeed, NMR allows the assignment of derivatization positions. 18,19 Although extensive work has been undertaken to characterize the properties and the applications of the -CD derivatives, and especially of the methylated and hydroxypropylated -CD, 20 little work has been done on ethylated--CD (Et--CD). [21][22][23][24] It has been shown that these Et-CDs can sustain the release of water-soluble drugs following subcutaneous 25 or oral administration.…”
Section: Introductionmentioning
confidence: 99%